Visual narrative through the Wimba approach in Tahilalats comic with campaign theme Bersama Stop Judi Online - Gumelar, Rangga Pangkuluhur; Prilosadoso, Basnendar Herry (citeus, 2025)
Comics, as a medium for conveying ideas and concepts through imagery, integrate textual and visual elements to construct meaning and communicate messages effectively. Their distinctive visual communication enables the delivery of complex social issues in an accessible manner through characters, panels, layouts, and visual representations of sound and dialogue. This study analyzes the Tahilalats comic (2024 edition), which incorporates the hashtag #bersamastopjudol as part of a visual campaign against online gambling addiction. The narrative is presented entirely through images without verbal language. The research applies Primadi Tabrani’s Wimba theory to decode visual language and Roland Barthes’ semiotics to interpret symbolic meanings. Findings indicate that comics can function as effective campaign tools, transmitting urgent social messages through minimalist yet impactful visual strategies. The Tahilalats comic demonstrates how visual storytelling, combined with layered semiotic structures, can engage audiences cognitively and emotionally without textual dependence. This study contributes to scholarly discourse on visual communication and public campaign media, offering insights into the capacity of comics to address sensitive and complex issues through concise and relatable visual narratives. The implications highlight the potential of visual media in shaping public awareness and behavior in contemporary digital culture.